Конфронтация „режима нормализации” и оппозиции в Чехословакии в конце 1980-х годов XX века - Zadorożniuk, Ella (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2004)
The paper refers to Russian and foreign archival documents, which became the basis for the analysis of relationships between the „party-and state authorities” and opposition in the Czech Republic in the late 80s of 20 th century. State authorities with conservative bias demanded that the „normalization” regime be stricter whereas „pragmatists” were contemplating a dialogue with the opposition. After the events of November 17 for a very long time also the followers of „non-political politics” in the opposition considered a dialogue with the pragmatic faction of the state authorities whereas the radical wing representatives were calling for immediate free elections and establishment of democratic institutions of power. However, it was the upward movement, beginning with the student demonstration of November 17, 1989 and ending with mass demonstrations which gathered as many as 700,000 people in Prague in the end of November, that gave momentum to historic transformation in the Czech Republic as it came up with its own hierarchy of historical priorities different from that of numerous government and opposition circles. These activists who were able to adjust their former standpoint to social expectations enjoyed public support.

W artykule, na bazie rosyjskich i zagranicznych archiwalnych dokumentów poddane zostały analizie relacje między „partyjno-państwowym kierownictwem” i opozycją w Czechosłowacji w końcu lat 80-tych. Konserwatywnie nastawieni przedstawiciele władz domagali się zaostrzenia reżymu „normalizacji”, natomiast „pragmatycy” brali pod uwagę dialog z opozycją. W opozycji zwolennicy „niepolitycznej polityki” też – do czasu wydarzeñ z 17 listopada, a także jeszcze długo po nich – brali pod uwagę dialog z nurtem pragmatycznym kierownictwa państwowego, natomiast zwolennicy radykalnego skrzydła domagali się natychmiastowego przeprowadzenia wolnych wyborów i formowania demokratycznych organów władzy. Ale właśnie ruch oddolny – począwszy od demonstracji studenckiej z 17 listopada 1989 roku i kończąc masowymi demonstracjami, gromadzącymi w Pradze w drugiej połowie listopada nawet po siedemset tysięcy uczestników nadawało w Czechosłowacji tempo przemianom historycznym, inaczej akcentując historyczne priorytety, niż to zakładały różne środowiska zarówno rządowe, jak i opozycyjne. Powodzeniem cieszyli się ci działacze, którzy, umieli skorygowaæ swoje poprzednie stanowisko zgodnie ze społecznymi oczekiwaniami.
Confrontation of the ''Normalization Regime'' and Opposition in the Czech Republic in the Late 80s of 20 th Century